PUTUSNYA PERKAWINAN KARENA MURTAD (Telaah Kritis Terhadap pasal 116 huruf â€œhâ€ Kompilasi Hukum Islam) - Rahmiati, Rahmiati (Alhurriyah, 2011)
According to fiqh, husband or wifeâ€™s appostation (murtad) becomes the marriage fasid (imperfect), void by law, while according to Compilation of Islamic Law article 116 letter â€œHâ€, â€œmurtad that makes unharmonious in the householdâ€ is one of reason for divorce. The word murtad it self should be enough to be a reason without any sentence â€œthat makes unharmonious in the household.â€. It is according to article 40 and 44 KHI (Compilation of Islamic Law) that forbidding interfaith marriage.